Oxidation Of Lead - Tin Solder Bumps In C4 Electronics Packaging - Yong, Su Kiat (2002)
The flip chip-on-board technology of using Sn-Pb solder bump is becoming more common in the electronic packaging industry owing to cost saving in cladded printed circuit. But problem that plague the electronics packaging industry, like the non-wet solder joints, extrusion, etc, need to be studied. Effects of environmental exposure of dies left in the tape and storage for prolonged period on the chemical stability and packaging have yet been studied.